Penerapan Sistem Akuntansi Pengeluaran Kas Atas Biaya Perjalanan Dinas Pada PT. Adhi Karya (Persero) Tbk - Talitha Irfanolita; Robert Pius Pardede (Program Vokasi dan LPPM IBI Kesatuan, 2022)
Adhi Karya (Persero) Tbk is one of the companies registered in the State-Owned Enterprises (BUMN) which is engaged in construction services, namely infrastructure development, EPC (engineering, procurement & construction), real estate and property. The accounting system used by PT. Adhi Karya (Persero) Tbk one of which is a cash disbursement system. Where the cash disbursement system in this company is to meet the operational needs of the head office, divisions and projects in cash. In this company, the activities of employees on official trips or duties are obligatory duties outside the area where they work. At PT. Adhi Karya (Persero) Tbk business travel activities can be said to be quite frequent which causes frequent cash disbursements transactions for official travel expenses. The purpose of this final project is to find out the application of the cash disbursement accounting system for official travel expenses, find out how cash disbursements are made for official travel costs or employee duties, and examine the suitability of the application process and cash disbursements for official travel expenses or employee duties with applicable regulations. Based on the results of practical work, it can be concluded that, all the rules and regarding the accounting system for cash disbursements for official travel costs at PT. Adhi Karya (Persero) Tbk has complied with the applicable regulations. Keywords : Cash Expenditure Accounting System, Official Travel Expenses